Political Energy Rhetoric and Market Reactions: Event Study of Global Equity, Fossil, and Renewable Assets - Akbar, Rasyidi Faiz (Journal of Economics, Business, and Government Challenges, 2025)
This study investigates the market reactions to Donald Trump’s 2024 presidential announcement, focusing on its impact on equity markets, coal, and clean energy assets. Given the limited research on how pro-fossil fuel political rhetoric affects both traditional and emerging energy sectors, this study highlights the spillover effects between fossil and clean energy markets. Using event study methodology, the analysis covers a 10-day window surrounding the announcement (t–5 to t+5), calculating abnormal returns (AR), average abnormal returns (AAR), and cumulative average abnormal returns (CAAR) across various markets. The results show positive abnormal returns in equity markets of Canada, China, and Saudi Arabia, reflecting optimism toward energy and trade policies. However, fossil fuel markets showed mixed reactions, with significant declines in crude oil and natural gas. Renewable energy assets, including Canadian Solar and First Solar, suffered losses, as did the electric vehicle and lithium sectors, particularly companies like Tesla and Tianqi. The findings contribute to the understanding of market sensitivity to political energy signals and offer valuable insights for investors and policymakers, with future research suggesting a need for exploring the long-term impact of policy shifts on market behaviour and stability.